A multi-pronged approach to addressing curricular challenges in undergraduate immunology education - Tonc, Elena; Chatterjea, Devavani (Frontiers in Education, 2025)
Immunology is typically offered as a single-semester course in non-immunology-focused graduate programs and as a module within foundational sciences or microbiology courses in conventional allopathic medical education. Undergraduate courses in immunology are frequently stand-alone upper-level lecture courses without an accompanying laboratory, and often leave students overwhelmed by the complicated molecular cascades and cell subsets. This creates a barrier for immune literacy among biology students, and students at large, all of whom are nonetheless impacted by the workings of their immune system every day, and stand to benefit from understanding how it functions. We addressed this barrier with a multi-pronged approach of elective immunology courses, first-year seminars, a majors’ survey course with a skills-based lab, advanced topical seminars, and an inquiry-based immunological research methods course. In this perspective article, we share our pedagogical practices to enhance immune literacy across all levels of a liberal arts and biology curriculum. Students can take one, several, or all of these courses during their undergraduate studies to build and bolster their understanding of immune systems and address the crucial need for increased scientific and immune literacy.